Kepastian Hukum Mekanisme Kerja Persekutuan Perdata Notaris Berkaitan Dengan pembuatan Akta - Christie Da Costa, Debora Natalia; &partners, Steviedacosta (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018)DO - 10.24843/AC.2018.v03.i02.p07, 2018)
The Civil Partnership in UUJNP indicates that Notaries can form a forum for cooperation. As time goes by the Notary work system that runs the Notary civil partnership is still questionable its validity, due to the arrangement of the civil partnership as regulated in the provisions of Article 16 paragraph (1) letter (f) and Article 20 paragraph (1), Article 40 UUJNP and 1618 KUH Perdata, not yet completely perfect and there are still deficiencies in implementation. The formulation of the problem, What is the mechanism of work of the Notary who runs the Notary Civil Partnership related to the confidentiality of making the deed according to Article 16 paragraph (1) letter (f) and Article 20 paragraph (1) UUJNP? and Is a legitimate Instrumenter witness who previously testified in the making of a deed by a colleague of the Notary Civil Partnership then reused by another Notary Civil Partnership partner reviewed under Article 40 of the UUJNP ?. This research is Normative Legal Research. The results of the study conclude that the mechanism of the Notary's work that reflects the character of the Notary Profession related to the confidentiality of making a deed in carrying out the Notary Civil Partnership according to Article 16 paragraph (1) letter (f) and Article 20 paragraph (1) UUJNP there is still a vague legal norm and the validity of previous Instrumenter witnesses has testified in the making of a deed by a colleague of the Notary Civil Partnership and then reused by other Notary Civil Partnership partners reviewed according to Article 40 of the National Law on Legal Entity, there is still ambiguity or obscurity of legal norms.